Formulation and In Vivo Evaluation of a Solid Self-Emulsifying Drug Delivery System Using Oily Liquid Tocotrienols as Model Active Substance - You Zhuan Lee; Eng Kwong Seow; Sheau Chin Lim; Kah Hay Yuen; Nurzalina Abdul Karim Khan (MDPI AG, 2021)
Self-emulsifying drug delivery systems (SEDDS) can improve the oral bioavailability of poorly water-soluble drugs. Solid self-emulsifying drug delivery systems (s-SEDDS) offer several advantages including improved drug stability, ease of administration, and production. Most compounds employed in developing s-SEDDS are solid in nature, with a high amount of surfactants added. The aim of this study was to develop an s-SEDDS using a tocotrienol-rich fraction (TRF) as the model liquid active substance via a simple adsorption method. The solid formulation was developed using magnesium aluminosilicate as the carrier with 70% TRF and 30% surfactants (poloxamer and Labrasol®). The formulation showed good self-emulsification efficiency with stable emulsion formed, excellent powder flowability, and small emulsion droplet size of 210-277 nm. The s-SEDDS with combined surfactants (poloxamer and Labrasol®) showed a faster absorption rate compared to preparations with only a single surfactant and enhanced oral bioavailability (3.4-3.8 times higher) compared to the non-self-emulsifying oily preparation when administered at a fasted state in rats. In conclusion, an s-SEDDS containing a high amount of TRF was successfully developed. It may serve as a useful alternative to a liquid product with enhanced oral bioavailability and the added advantage of being a solid dosage form.